Strengthening Institutional Capacity of the North Kalimantan Provincial Department of Manpower and Transmigration in Performing Employment Sector Functions - Ernaldiwan, Fauzi; Haning, Muh. Thahir; Ibrahim, Muh. Akmal; Nara, Nurdin; Iskandar, Didik (Journal La Bisecoman, 2024)
Organizational capacity development is a crucial element in improving the effectiveness of public services, especially for strategic institutions such as the Manpower and Transmigration Office (Disnakertrans). This research aims to deeply analyze the capacity development of the North Kalimantan Province Manpower and Transmigration Office in carrying out its duties and functions in the employment sector. Using a descriptive qualitative approach, this study adopted Potter and Brough's (2004) Systemic Capacity Building model which includes nine elements of capacity. Data were collected through in-depth interviews with key informants, observation, and documentation, then analyzed using an interactive model. The results showed that the Kaltara Disnakertrans has good capacity at the structural, system and role levels, characterized by the existence of collaborative forums and a clear division of tasks. However, significant challenges are still found in the foundational elements, namely performance capacity (limited human resources, budget, and equipment) and facility capacity (the absence of a provincial Vocational Training Center), which has implications for workload capacity. This study concludes that capacity development in the Disnakertrans of Kaltara has not been operationally optimized due to an unsound resource foundation, thus requiring a holistic approach that strengthens internal and external capacity simultaneously.